Diabetic adolescents and their families : stress, coping, and adaptation - Seiffge-Krenke, Inge (Cambridge studies on child and adolescent health., 2001)
Diabetic Adolescents and their Families presents an innovative approach to the study of coping with chronic illness by focusing on the developmental context in its description of a longitudinal study of families with a diabetic or a healthy adolescent. Inge Seiffge-Krenke considers perspectives of the ill adolescents, their parents, and the physicians treating them. Highlighted topics include typical stressors, individual and family coping strategies, and psychosocial consequences associated with diabetes. The author also examines the changes that occur in adolescents' self-concept and body image and analyses their relationships with parents, physicians, friends, and romantic partners as sources of support and of stress. Numerous case studies illustrate the difficulty of balancing normative development and adherence to the therapeutic regimen. Integrating clinical concerns with fundamental findings of developmental psychology, this book will be of value to anyone with an interest in the study of adolescent health psychology.